Nursing Care for Neonate with Gastroschisis - Phansang, Kandamanee; Keskomon, Thipkhumporn; Tamsat, Aphisit (Journal of The Royal Thai Army Nurses, 2020)
Gastroschisis is an abnormal condition of neonate with a hole in the congenital abdominal wall. It results from an abnormality in the umbilical vein or a ruptured umbilical hernia sac. It defects the anterior abdominal wall in every layer. Therefore, the intestine protrudes from the abdominal wall and is swollen, inflamed, or infected. The doctor can detect this condition in the antenatal period and after delivery. After birth, preventing hypothermia, infection, and lack of water and nutrients is very important. After the abdominal wall closed surgery, nursing care focuses on preventing hypoxia due to decreased breathing efficiency. It can occur because of re-entering the intestine into the abdomen cavity. That can make the chance of increased intra-abdominal pressure. The register nurses have to monitor the abdominal compartment syndrome, wound infection, and lack of water and nutrition due to the dysfunction of the intestine. Before discharging the neonate, nurses should assess the parents’ knowledge, anxiety, and readiness to care for their newborn at home and encourage them to care for the newborn’s safety.